The Effectiveness of Powerpoint-Based Audio Visual Media on Science Learning Outcomes on Solar System Material in Class VII Students - Sinaga, Feliza Paramitha; Tosin, Adelakun Isaac; Das, Amit Kumar (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: To determine the effectiveness of power point-based audio visual media on student learning outcomes regarding the solar system in class VII in junior high school Methodology: This type of research is quantitative research with a quasi experimental research method. The research carried out involved two classes, a control class and an experimental class. Simple random sampling technique. The class that is the control class is class VII C while the class that is the experimental class is class VII D. The instruments used in this research were questionnaires and questions. The data collection method for this research was carried out using pretest and posttest. The data analysis technique used in this research is the T-test using the SPSS program. Main Findings: Main findings of this study reveal that the use of PowerPoint-based audiovisual media significantly enhances students' learning outcomes in the Solar System topic. Statistical analysis shows a significant difference between the experimental and control groups, with higher scores for the experimental group. The media effectively improves understanding of complex materials and increases student motivation. This practical, interactive approach highlights the potential of simple technology in science education, providing new empirical evidence and a scalable solution for improving learning in diverse educational contexts. Novelty/Originality of this study: This research is the basis for developing a science study on learning media regarding the solar system using Power Point learning media for class VII junior high school students.